Nutritional Deficiencies in Children of the First 3 Years of Life, According to a Multicenter Study in Ukraine - S.L. Nyankovsky; D.O. Dobriansky; O.S. Ivakhnenko; M.O. Yavorska; V.V. Zayets; O.M. Platonova; O.G. Shadrin; V.A. Klymenko; G.L. Solodovnik (Zaslavsky O.Yu., 2015)
Taking into account the fact that in Ukraine today there is not enough researches that summarize the data on the nutritional status of young children, the prevalence of eating disorders and lack of basic macro- and micronutrients in children, the multicenter study on nutrition of children from 9 months to 3 years of life has been carried out. It was found that the present dietary intake of infants is unbalanced, contains excess energy and proteins, lack of zinc, iron, calcium, and vitamins A, D, E, B6, B12, B1. Due to unbalanced diet, the use of special infant formula instead of unmodified bovine milk in feeding young child can increase consumption of important nutrients (calcium, iron, iodine, vitamin E, D and folates).